Oxidative stress biomarkers in pulmonary tuberculosis patients in Gombe, North-eastern Nigeria - Yeldu, Mohammed Haruna; Ibrahim, Yakubu; Akuyam, Shehu Abubakar; Danasabe, Isah Muhammad; Shehu, Buhari; Danjuma, Mohammed; Bello, Miftahu; Yahaya, Usman (Asian Journal of Medical Sciences, 2019)
Background: Oxidative stress may play an important role in the pathogenesis of pulmonary tuberculosis (PTB). To our knowledge there is paucity of data on the status of oxidative stress biomarkers among PTB patients in Gombe, North-eastern Nigeria. Our study was designed to evaluate the oxidative stress biomarkers in pulmonary tuberculosis patients in Gombe, North-eastern Nigeria. Aims and Objectives: To determine the serum levels of oxidative stress biomarkers among patients with pulmonary tuberculosis in Gombe metropolis, North-eastern Nigeria and to assess the correlation between the oxidative stress biomarkers in pulmonary tuberculosis patients. Materials and Methods: A cross sectional comparative study was conducted in a tertiary health care facility with 40 pulmonary tuberculosis (PTB) patients on anti-TB drugs treatment (ATT), 40 newly diagnosed PTB patients not yet on anti-TB drugs treatment (ATT-naïve) and 40 age- and sex-marched apparently healthy subjects (controls). Serum total antioxidant status (TAS), total oxidant status (TOS), malondialdehyde (MDA), nitric oxide (NO) and oxidative stress index (OSI) determined using standard techniques. Data was analysed using INSTAT® (Graph Pad Software Inc., La Jolla, CA, USA). Results: Serum levels of TOS, OSI, MDA and NO were significantly (p ˂ 0.001) increased in PTB patients (ATT and ATT-naïve) when compared with healthy individuals. Serum TAS and body mass index (BMI) were significantly (p ˂ 0.001) decreased in PTB patients when compared with healthy individuals. Serum TOS significantly correlated with serum OSI, MDA and NO in ATT-naïve PTB patients. Conclusion: This study observed an increased oxidative stress biomarkers and decreased total antioxidant status in newly diagnosed pulmonary tuberculosis patients and those on treatment. Our findings suggest that antioxidants supplementation and improved nutrition in the management of pulmonary tuberculosis patients may go a long way in preventing the oxidative onslaught and further complications in PTB patients.